Rare case of remission of a patient with small cell carcinoma of the ovary, hypercalcaemic type (SCCOHT) stage IV: Case report. (2020) - Mathey, M.P.; de Jolinière, J. Bouquet; Major, A.; Conrad, B.; Khomsi, F.; Betticher, D.; Devouassoux, M.; Feki, A.
Highlights: Small cell carcinoma of the ovary is a very rare, highly undifferentiated, aggressive malignancy that affects young women and linked to a poor prognosis (especially women under 40 years of age). We present a 22 years old African woman with complete remission 30 months after diagnosis despite a conservative surgery and only 3 cycles of chemotherapy. SCCOHT seems to be a monogenic disease with mutations in the tumour suppressor gene, a chromatin remodeler: SMARCA4 and can involve germline or somatic lines. Mutation can also be a de novo sequence. Research for new treatments includes target therapy. Because of the rareness of SCCOHT (about 300 cases in the world) no standard treatment guidelines for SCCOHT are established, but combination of surgical debulking and chemotherapy based on cisplatin, are common practice. Autologous stem cell transplant after high-dose adjuvant chemotherapy seems to lead to the best survival rates, because it allows perform doses 2- to 10-fold higher than standard chemotherapy doses. Abstract: Introduction: Small cell carcinoma of the ovary (SCC) is a very rare (less than 1 % of ovarien neoplasia), highly undifferentiated, aggressive malignancy affecting young women and linked to a poor prognosis. Overall survive rate is very low (about 16 %). SCCOHT has recently been shown to be associated with SMARCA4 gene mutations and shows some genetic similarities to malignant rhabdoid tumors (MRT). Presentation of case: After a reminder of the clinical, histological description of the SCCOHT and concensus about the medical management, we describe the rare case of a 22 years old patient with complete remission after diagnosis of un undifferentiated SCCOHT stage IV treated by conservative surgery and high-doses chemotherapy, 30 months after diagnosis. Discussion: Thus far, no standard therapy exists for SCCOHT. Treatment modalities are surgery, chemotherapy, radiotherapy and autologous stem cell transplant after high-dose chemotherapy. Research for new treatments includes target therapy. Conclusion: Autologous stem cell transplant after high-dose adjuvant chemotherapy seems to lead to the best survival rates. Invasiveness of the treatment depends on the stage of the disease, age of the patient and her fertility-sparing desire. An international collaboration will be needed to standardise practices due of the small number of patients.